Woman as Charismatic Leader at Pesantren - Hanifah Siti Nur Rohmah (The Institute of Research and Service Community IPMAFA Pati, 2020)
Islamic Boarding School is an Islamic educational institution that shows the existence of a subculture in Indonesia. When the wider community proudly declares realistic and calculated positivism, without circumventing this, Islamic Boarding School is one of the institutions that are still strong and remain proud of the concept of charisma. This becomes very interesting to study about this them, especially when a leader who is considered charismatic is a woman. This research was conducted to know the charismatic leadership of Nyai Hj. Umi Azizah at the Al-Khodijah Dormitory, An Nur Islamic Boarding School. The research was conducted using qualitative research methods with data collection techniques of observation, interviews, and documentation. Data analysis used the analytical technique developed by Miler and Huberman, namely performing data reduction, presentation, and verification. The analysis was carried out with the approach of the charismatic leader Max Weber. From this research, it is known that Nyai Umi is considered to have charisma by her followers, including her extraordinary ability to listen, guarded by supernatural beings, brings blessings, and has loyal followers.